2014
DOI: 10.1002/hed.23570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2 different swallowing exercise regimens during organ‐preservation therapies for head and neck cancers on swallowing function

Abstract: Findings indicate significant benefits of the exercise group's exercise regimen in reducing PEG dependence and oral intake difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 81 publications
2
46
0
1
Order By: Relevance
“…As an example, aggressive preventative therapy may ameliorate the soft tissue toxicities in the arena of dysphagia as patients who maintain active swallow efforts throughout the course of radiation and into early recovery have improved swallowing outcomes. [21][22][23] Although the exact mechanism by which proactive swallow therapy enhances long-term outcomes is unknown, it may be postulated that swallowing exercises result in improved lymph flow with decreased acute edema and chronic lymphedema, prevention of constrictive fibrosis, and limiting muscular atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, aggressive preventative therapy may ameliorate the soft tissue toxicities in the arena of dysphagia as patients who maintain active swallow efforts throughout the course of radiation and into early recovery have improved swallowing outcomes. [21][22][23] Although the exact mechanism by which proactive swallow therapy enhances long-term outcomes is unknown, it may be postulated that swallowing exercises result in improved lymph flow with decreased acute edema and chronic lymphedema, prevention of constrictive fibrosis, and limiting muscular atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…As it is generally agreed that prolonged disuse is detrimental to swallow function in the HNC population [21], there has been increasing interest in the potential benefit of prophylactic swallowing interventions conducted intensively during and early post-treatment to reduce dysphagia in patients treated with primary CRT [4, 2230]. Several studies have found some positive results with varying degrees in functional outcomes [4, 2226, 28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found some positive results with varying degrees in functional outcomes [4, 2226, 28, 29]. Specifically, some of these studies suggested that patients who underwent CRT and adhered to a swallowing exercise program during and/or after treatment returned to an oral diet sooner, had improved weight gain, shorter duration of gastrostomy tube use, and/or exhibited higher quality of life scores [22, 2427, 29, 30]. Additionally, less floor of mouth muscle deterioration with the implementation of prophylactic swallow exercise protocols has been shown [22].…”
Section: Introductionmentioning
confidence: 99%
“…This was in the context of a research protocol and translation to clinical practice is likely to be challenged by resource limitations. A more recent study provided a program whereby exercises were supervised for 45 min, once a week by an SLP [34]. Patient adherence to preventive swallow exercises during and after treatment remains challenging.…”
Section: Considerations In Dysphagia Managementmentioning
confidence: 98%
“…Active promotion of swallowing and swallowing exercise [28,33,34] Optimizing analgesia in the acute phase [31] Pretreatment counselling and rigorous baseline assessment [35,36] Minimize oral mucositis [37] Psychological care [38] Lymphoedema therapy [39,40] Acupuncture for xerostomia and pain [41] [24,25 & ,26] Question Response…”
Section: Considerations In Dysphagia Managementmentioning
confidence: 99%